The Entrepreneurship and poverty reduction nexus - KHAN, Md. Abu Nashir (KDI School, 2017)
This paper argues that poverty in a country is endogenously determined by the country’s long-term economic development strategy. It empirically examines the effects of entrepreneurial activities on its level of poverty. This paper also examines how this effect of entrepreneurial activities differs with the level of financial development in an economy, which is the most important channel for the effects of entrepreneurial activities on poverty to manifest themselves. Data for the period of 2000 to 2013 from 37 countries are used in the analysis. We find that the more entrepreneurial activities, the higher the level of poverty incidence. But a high level of financial development reduces the poverty-increasing impact of adopting entrepreneurial activities. The policy recommendation of this paper is government should create an environment that facilitates the growth and poverty reduction based on their entrepreneurial activities or entrepreneurship, which facilitates the actors’ entry into an industry according to the economy in order to reduce poverty incidence.
Thesis(Master) --KDI School:Master of Public Policy,2017